Sex differences in the effects of mental fatigue on single-leg drop landing biomechanics among sport science university students - Wang, Zilong; Feng, Ziqi; Cui, Huizi; Meng, Lingyue; Wang, Pengfei; Lu, Mengya; Liu, Tao; Zhang, Qiuxia; Wang, Xiangdong (Frontiers in Psychology, 2025)
ObjectiveTo investigate the sex-differentiated effects of Mental Fatigue (MF) on lower extremity biomechanical characteristics during single-leg drop landing among sport science university students.MethodsTwenty-eight healthy sport science university students (14 females, 14 males) performed single-leg drop landings from a 30 cm height before and after MF induction via a 45-min Stroop task. Kinematic and kinetic data during landing were synchronously captured using a Vicon infrared motion capture system and Kistler force plates. A 2 × 2 mixed-design analysis of variance (ANOVA) was employed.ResultsAt Initial Contact (IC), males exhibited significantly smaller ankle plantarflexion angles post-MF compared to baseline (p < 0.001), and also significantly smaller than females post-MF (p = 0.005). Post-MF, females exhibited significantly smaller knee flexion angles than males (p = 0.004). For ankle inversion angle, only a significant main effect of sex was observed (p = 0.004). No significant differences were found for hip angles or kinetic variables at peak vGRF.ConclusionAt IC, males compensated by reducing ankle plantarflexion, while females compensated by reducing knee flexion, indicating that MF induces a sex-specific strategic reorganization of distal-proximal joint control. These differences disappeared during the peak loading phase, suggesting that MF primarily affects early anticipatory mechanisms rather than the entire impact absorption process. Ankle inversion angle showed only a sex main effect, and hip strategy remained unchanged, further highlighting a hierarchical control logic prioritizing “ankle-knee first, hip later.” This study not only validates the existence of an MF × sex interaction effect but also underscores the theoretical value of non-significant indicators under the null hypothesis.